KH. Hasyim Asy'ari and John Dewey: Traditionalism and Progresivism In Education - Neneng Nurhayati; Benny Prasetya; Heri Rifhan (PT. Caesarindo Triloka Persada, 2026)
This study aims to analyze and compare the educational thought of KH. Hasyim Asy’ari and John Dewey, focusing on the tension and dialogue between traditionalism and progressivism in education. The primary problem under study concerns how two influential figures from different socio-cultural and intellectual backgrounds conceptualize the aims, methods, and values of education, and how their ideas remain relevant in contemporary discourse. Existing scholarship often positions KH. Hasyim Asy’ari as a representative of Islamic traditionalism and John Dewey as a pioneer of educational progressivism; however, few studies critically juxtapose their frameworks to identify convergences and potential synthesis. This research employs a qualitative library method with a comparative-philosophical approach, analyzing primary texts and relevant secondary sources to reconstruct their educational paradigms. The findings reveal that while KH. Hasyim Asy’ari emphasizes moral-spiritual formation rooted in tradition and religious authority, and John Dewey prioritizes experiential learning and democratic values, both share a commitment to character development and social responsibility. The study contributes a novel integrative perspective that bridges traditional Islamic pedagogy and modern progressive education within contemporary educational theory.